Способ получения смесевого твердого топлива - Архипов В. А. Владимир Афанасьевич; Ворожцов А. Б. Александр Борисович; Горбенко Т. И. Татьяна Ивановна; Коротких А. Г. Александр Геннадьевич; Савельева Л. А. Лилия Алексеевна; Сакович Г. В. Геннадий Викторович
опубл. 20.09.11